Studi Empiris Penggunaan Framework pada Website Jaringan Dokumentasi dan Informasi Hukum Daerah Pulau Jawa - Minokaura, Muh. Fachrul; Afisina, Annisa; Rahman, Arief; R., Echa Alfa; Rizal, Muhammad Ainur; Rakhmawati, Nur Aini (Laboratorium Ilmu Komunikasi, Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) Universitas Ha, 2020)
In order to provide information on cross-sector legislation that can be accessed by the public, the National Legal Development Board (BPHN) has created a national-level website jdihn.go.id. But currently there are JDIH websites in each district and city. Therefore, we conducted a website survey in each district and city in Java. Java Island itself has 119 regencies and cities (85 regencies and 34 cities). We find out the web technology used in each JDIH district and city web sites, such as web servers, web programming languages, CSS, content management systems and web frameworks using the Wappalizer application and from the results of the analysis it is concluded that the JDIH website in Java has used a framework according to website standard requirements.Keywords— Framework, JDIH, Analyze, Website